2007
DOI: 10.1124/dmd.107.015230
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Glucuronidation Is Minimally and Nonselectively Inhibited by the Fibrates Gemfibrozil, Fenofibrate, and Fenofibric Acid

Abstract: ABSTRACT:Gemfibrozil coadministration generally results in plasma statin area under the curve (AUC) increases, ranging from moderate (2-to 3-fold) with simvastatin, lovastatin, and pravastatin to most significant with cerivastatin (5.6-fold

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…However, some reports about gemfibrozil's effects on UGTs are available. Goosen et al (2007) have recently reported that gemfibrozil inhibited atorvastatin lactonization and atorvastatin lactone glucuronidation with IC 50 values of 346 and Ͼ1000 M, respectively. The highest rates of lactonization or atorvastatin lactone glucuronidation were mediated by UGT1A1 and UGT1A3, or UGT1A3 and UGT1A4, respectively (Goosen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some reports about gemfibrozil's effects on UGTs are available. Goosen et al (2007) have recently reported that gemfibrozil inhibited atorvastatin lactonization and atorvastatin lactone glucuronidation with IC 50 values of 346 and Ͼ1000 M, respectively. The highest rates of lactonization or atorvastatin lactone glucuronidation were mediated by UGT1A1 and UGT1A3, or UGT1A3 and UGT1A4, respectively (Goosen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Goosen et al (2007) have recently reported that gemfibrozil inhibited atorvastatin lactonization and atorvastatin lactone glucuronidation with IC 50 values of 346 and Ͼ1000 M, respectively. The highest rates of lactonization or atorvastatin lactone glucuronidation were mediated by UGT1A1 and UGT1A3, or UGT1A3 and UGT1A4, respectively (Goosen et al, 2007). The study by Prueksaritanont et al (2002b) showed that gemfibrozil inhibited simvastatin glucuronidation (IC 50 ϭ 354 M); simvastatin is mainly glucuronidated by UGT1A1 and UGT1A3.…”
Section: Discussionmentioning
confidence: 99%
“…Because in HF diet-fed dmd.aspetjournals.org rats treated with fluvastatin for 8 days, the decrease in hepatic levels of CYP2Cs was moderate but that in CYP3As was extensive, the administration of other statins such as simvastatin, lovastatin, and atorvastatin to HF diet-fed rats might cause more severe adverse effects. The dihydroxy heptanoic or heptenoic acid side chain of statin hydroxy acids is a structural feature common to all statins, which undergo glucuronidation to form an acyl glucuronide conjugate and lactonization to form a statin hydroxy acid lactone by human UGT1A1, UGT1A3, UGT1A4, UGT1A8, UGT1A9, and UGT2B7 (Prueksaritanont et al, 2002;Goosen et al, 2007). Riedmaier et al (2010) have demonstrated that lactonization of atorvastatin is catalyzed mainly by UGT1A3 in humans and affected by polymorphisms at the UGT1A locus.…”
Section: Discussionmentioning
confidence: 99%
“…Atorvastatin, lovastatin, and simvastatin are oxidized mainly by CYP3A4 (Fischer et al, 1999) and their glucuronidation is catalyzed mainly by human UGT1A1 and UGT1A3 (Prueksaritanont et al, 2002). Although a potent inhibitor of CYP3A4 can significantly increase the plasma concentrations of the active forms of atorvastatin, lovastatin, and simvastatin, which are oxidized mainly by CYP3A4 (Kyrklund et al, 2001;Backman et al, 2002;Goosen et al, 2007), fluvastatin is oxidized mainly by CYP2C9 (Spence et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Gemfibrozil 1-0-β glucuronide and, to a lesser extent, the parent compound are also potent inhibitors of OAT1B1/3-mediated hepatic uptake of statin acids, as well as OATP2B1, Na+-taurocholate cotransporting polypeptide, the renal transporter OAT3, and statin glucuronidation or lactonization. 52,53 Thus, DDIs, including hepatotoxicity and muscle-related toxicity, in patients receiving statin-gemfibrozil combination therapy may vary as a result of differences in statin susceptibility to inhibitory effects of intestinal, hepatic, and renal transporters, as well as CYP450 metabolism.…”
Section: Gemfibrozilmentioning
confidence: 99%